Tinjauan terhadap Pelaksanaan Peraturan Daerah Sumatera Barat No. 9/2014 tentang Serah Simpan Karya Cetak dan Karya Rekam - Eddy Imanuel Doloksaribu; Lidwina Maria T; A Aris Swantoro; Tisa Windayani (Jurnal Perkotaan, 2018)
Abstract The effort to acknowledge as well as to protect intellectual works have been done not only in the view of protecting the so-called intellectual property rights but also preserving the works itself. For the later, the attempt is represented in Law No 4/1990 which obligate publishers and recording companies to deposit a stipulated number of copies of their work in determined libraries. This national level policy followed by quite a lot of provinces resulting in the formation of regional regulations concerning the same matter. However, only few of those use criminal law instrument. Since this is a multiperspective research, Regional Regulations of Sumatera Barat No. 9/2014 is deemed to fit the study because it comprises criminal provisions, business law aspects, and also private law issues. This research examines the implementation of the law from three standpoints: i) the implementation of the criminal provisions, ii) how its implementation protects the rights of the owner of the works as well as their benefit from the view of business law, and iii) the private legal relation between the parties of deposit arrangements. The research found that: i) the criminal provisions have not been enforced because the authority has not been equipped by civil investigator; ii) Dinas Kearsipan&Perpustakaan Kota Padang has done full effort in registering the works in order to have them deposited in the library, eventhough constraints related to budget delimitates the attempt. By this reason the protection and benefit for the owner has not been fully achieved; iii) there is neither special agreement nor any arrangement found in the relation between parties. Keywords: implementation of Perda Sumbar No 9/2014; intellectual works deposite.